Macrophage skewing by Phd2 haplodeficiency prevents ischemia by inducing arteriogenesis - Takeda, Yukiji (2011)
The authors are thankful to Dr. P. Carmeliet for scientific discussion and support. VE-Cadherin:CreERT and PDGFRB:Cre transgenic mice were generated at the Cancer Research UK (London, UK) and kindly donated by Dr. R. Adams. The IKKβ floxed mice are a generous gift of Dr. M. Karin (UCSD, La Jolla, CA). The hydroxylase-deficient PHD2 construct was given by Dr. P. Ratcliffe (Oxford, UK).